THE INFLUENCE OF METEOROLOGY VARIABLES TO ANNUAL PARASITE INCIDENCE IN KUPANG DISTRICT, EAST NUSA TENGGARA PROVINCE - Cahyorini
Malaria is caused by parasites of the genus Plasmodium. Value of Annual Parasite Incidence (API) is used to divide the stratification of malaria in Indonesian territory. Eastern Indonesia include in high malaria stratification. Local climatic conditions can improve or affect mosquito breeding habitats thereby disrupting the balance of vector populations and malaria transmission patterns. Climate variables that can be used to predict malaria transmission are rainfall, temperature, humidity and rainy days. The value of APIs for 11 years was noted that 7 years of which were in high endemic stratification API> 5 °/oo. Value of the correlation between climate variables with the highest API score is with rainy days variable (r = -0.347) and the lowest with a temperature variable (r = -0.043). Value of the correlation between climate variables with the highest value of the AFI is with variable rainy days (r = -0.330) and the lowest with a variable temperature (r = -0.032). Value of the correlation between climate variables with the highest value is PvAPI with variable rainy days (r = -0.351) and the lowest with a variable temperature (r = -0.061). The results obtained from simple linear regression equation is Y = 6.458 to 0.356 x Rainy Day dan Y = 16.99-0.987 x Humidity. R2 values obtained from the multiple linear regression analysis of each value of the API, AFI, PvAPI ranged from 23 to 25.7% may explain the variable value of the API, AFI and PvAPI. We can used SD value to predict API value = 3.79 o/oo means that there are 4 from 1000 people who have a risk of malaria within a period of one year. AFI values used SD value of 2.54 o/oo, which means that 3 of the 1000 people who have a risk of malaria within a period of one year. PvAPI value used SD value of 1.35 o/oo which means that 2 of the 1000 people who have a risk of malaria within a period of one year.